2020
DOI: 10.1016/j.psj.2019.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the quality characteristics of chicken breast meat from conventional and animal welfare farms under refrigerated storage

Abstract: In this study, we aimed to investigate the meat quality characteristics, bioactive compound content, and antioxidant activity during refrigerated storage of breast meat of Arbor Acres broilers (carcass weight: 1.1 kg, raised for 35 D) obtained from a conventional farm ( BCF , n = 30) and an animal welfare farm ( BAF , n = 30) in Korea. The BCF and BAF did not differ in their proximate composition, color, water-holding capacity, creatine, creatinine, and carnosine c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 36 publications
3
52
2
3
Order By: Relevance
“…Generally, vacuum packing and the precise temperature control used in the SV treatment of meat products can inhibit lipid oxidation and aerobic bacterial growth during storage, which improve storage stability [3,25]. TBARS concentration is generally used as an indicator of lipid oxidation extent in meat products, which is positively correlated with off-flavor intensity [19,26]. In the current study, SV pork patties with searing tended to exhibit lower TBARS contents compared to patties without searing at 0 and 49 d of cold storage (p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, vacuum packing and the precise temperature control used in the SV treatment of meat products can inhibit lipid oxidation and aerobic bacterial growth during storage, which improve storage stability [3,25]. TBARS concentration is generally used as an indicator of lipid oxidation extent in meat products, which is positively correlated with off-flavor intensity [19,26]. In the current study, SV pork patties with searing tended to exhibit lower TBARS contents compared to patties without searing at 0 and 49 d of cold storage (p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…The cell was horizontally shaken and incubated at 37 • C for 2 h. The mixture was titrated with 0.02 N H 2 SO 4 . The experiment was conducted in triplicate, and VBN content was calculated using a method previously described by Kim et al [19]. Then, 10 g of SV cooked patty was homogenized with 90 mL sterilized saline solution using a homogenizer (Pulsifier PUL100E, Microgen Bioproducts Ltd., Surrey, UK).…”
Section: Storage Stabilitymentioning
confidence: 99%
“…Comparando os resultados do estudo, com os outros semelhantes (Pereira, et al, 2006;Limoni, et al, 2017;Zhang, et al, 2018), pode-se notar que o leve aumento do pH ou sua estabilidade podem ocorrer devido a redução das reservas de glicogênio ainda presente no músculo.Em relação a coloração, este é um dado que deve ser considerado devido à importância comercial já que o consumidor, ao comprar gêneros alimentícios, é atraído pelo aspecto visual (Kim, et al, 2020;Rodrigues & Pozza, 2020;Salueña, et al, 2019). Neste sentido, os valores de a*>0 indicam que foram positivos e predominaram a coloração vermelha, característica da carne e mais atraente na hora da compra, estes dados podem ser observados na Figura 1.…”
Section: Valores De Ph E Cor Durante O Armazenamentounclassified
“…A amostra OCB apresentou uma maior estabilidade em seus valores, iniciando com 42,7 ± 0,8 aos primeiros 20 minutos, ao 4º dia, 41,55 ± 0,91 e ao 7º dia, 40,58 ± 7,11. No Al-Hijazeen, et al, 2016;Kim, et al, 2020). Desse modo, os resultados encontrados no presente estudo podem estar relacionados a baixa dosagem, uma vez que segundo Burt (2004), para obter resultados favoráveis podem ser necessárias mais que duas vezes a dosagem bactericida encontrada in vitro para aplicação efetiva nos alimentos.…”
Section: Valores De Ph E Cor Durante O Armazenamentounclassified
“…pH is closely related to the quality of meat, and parameters such as the water-holding capacity and age are instrumental for evaluating meat quality [14]. Kim et al [10] reported that the pH of the KNBG loin is 5.5. In the present study, the pH of ribs was 6.21-6.46, which is higher than that of the loin.…”
Section: Meat Quality Of Knbgs Ribs Segregated Based On Sexmentioning
confidence: 99%